2011
DOI: 10.1007/s00253-011-3297-0
|View full text |Cite
|
Sign up to set email alerts
|

Improved expression of secretory and trimeric proteins in mammalian cells via the introduction of a new trimer motif and a mutant of the tPA signal sequence

Abstract: Ideal immunogenicity in antigens is a prerequisite to eliciting a sufficiently strong immune and memory response via either DNA or protein vaccines. To improve immunogenicity, efforts have focused on high-level expression of target proteins and on maintaining their natural conformations. In the present work, two trimer motifs (MTQ and MTI) were designed and introduced into a plasmid vector with the tissue plasminogen activator signal peptide (tPA-SP). Next, we examined the efficacy and the efficiency of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…Various studies have shown that truncation of the HIV Env from gp160 to gp150 increases the levels of expression on the surface of virus particles [10,32]. In addition, the replacement of the native HIV Env leader sequence with other leader sequences has also been shown to increase expression [10,33,34]. The use of the flexible glycine linker sequence is also expected to prevent the shedding of the gp120 portion of the HIV Env trimer from the surface of the VLPs [23], resulting in higher levels of detection of gp120 on the surface of the VLPs.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that truncation of the HIV Env from gp160 to gp150 increases the levels of expression on the surface of virus particles [10,32]. In addition, the replacement of the native HIV Env leader sequence with other leader sequences has also been shown to increase expression [10,33,34]. The use of the flexible glycine linker sequence is also expected to prevent the shedding of the gp120 portion of the HIV Env trimer from the surface of the VLPs [23], resulting in higher levels of detection of gp120 on the surface of the VLPs.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant Py S4/CelTOS and TRAP was produced in suspension HEK293F cells cultures, as previously described (Harupa et al, ; Kaushansky et al, ). Briefly, an expression construct containing a tissue plasminogen activator signal (Wang et al, ), the extracellular domain of Py S4/CelTOS (PlasmoDB:PYYM_1436300, amino acids 25–185) or TRAP (PlasmoDB:PYYM_1351500, residues 23–752), and a C‐terminal His tag followed by an AviTag (Beckett, Kovaleva, & Schatz, ) cloned into the pcDNA‐3.4 vector backbone (Thermo Fisher, Waltham, MA, USA) was introduced into HEK293F cells by high‐density transfection with PEI MAX 40000 (Polysciences, Inc., Warrington, PA, USA; Backliwal, Hildinger, Hasija, & Wurm, ; Carbonetti, Oliver, Glenn, Stamatatos, & Sather, ). Cell cultures were then grown for 5 days before purification of the protein from culture supernatants by Ni‐affinity chromatography followed by size exclusion chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…Altering the signal peptide sequence has previously been shown to increase secretion for some proteins [40, 41]. We exchanged the natural signal peptide of sCD4 with three commonly used signal peptides and analyzed the resulting amino acid sequences with the bioinformatics program SignalP, which discriminates secreted from non-secreted proteins [42].…”
Section: Resultsmentioning
confidence: 99%